Answer:
y=3/2x+1
Step-by-step explanation:
y-4= -⅔(x-6)
y-4=-⅔x+4
y=-⅔x+4+4
(equation of line 1) y= -⅔x+8 gradient= -⅔
(line 2)gradient=3/2
note* the gradients of perpendicular lines multiplied result to -1
gradient=<u>y²-y²</u>
<u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u>x²-x¹
<u>3</u><u> </u>=<u>y</u><u>+</u><u>2</u>
<u> </u><u> </u>2. x+2
multiply both sides by 2(x+2)to remove the denominators
3(x+2)=2(y+2)
3x+6=2y+4
3x+6-4=2y
3x+2=2y
divide all sides by 2
3/2x+1=y
y=3/2x+1
2. You simplified parenthesis on both sides
3. Subtracted 14 from -25 on right side
6. Divided each side by 9
Answer:
a) (-9,3)
Step-by-step explanation:
x + 2y = -3
- (x - y = -12)
<u />
x + 2y = -3
<u>- x + y = 12</u>
3y = 9
y = 3
x - y = -12
x- 3 = -12
x= - 9
(-9, 3)
Hope I helped with your problem
Step-by-step explanation:
Given that,
Directrix, d= -5, and eccentricity, e = 2.
The polar equation of the conic is given by :

Put all the values,

As e>1, it is a hyperbola. Hence, this is the required solution.